2020
DOI: 10.3390/agronomy10071002
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary LED Interlighting Improves Yield and Precocity of Greenhouse Tomatoes in the Mediterranean

Abstract: In Northern Europe, the use of light–emitting diodes (LEDs) is widely adopted in protected horticulture, enabling to enhance plant growth by ensuring needed radiative fluxes throughout seasons. Contrarily, the use of artificial lighting in Mediterranean greenhouse still finds limited applications. In this study, the effects of supplemental LED interlighting on vegetative development, fruit growth, yield, and fruit quality of high-wire tomato plants (Solanum lycopersicum L. cv. ‘Siranzo’) during spring and summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 41 publications
7
32
0
1
Order By: Relevance
“…Considering this parameter, generally, plants grown with SL showed higher values than under NL ( Figure 6). The same results were obtained from Paucek et al [34] with supplemental LED inter-lighting. Like most growth processes, fruit development is dependent on temperature [28], and, at same time, tomato fruit are capable of photosynthesis and may contribute up 20% to the fruit photosyntate content [34].…”
Section: Plant Growth Yield and Light Efficiencysupporting
confidence: 88%
See 3 more Smart Citations
“…Considering this parameter, generally, plants grown with SL showed higher values than under NL ( Figure 6). The same results were obtained from Paucek et al [34] with supplemental LED inter-lighting. Like most growth processes, fruit development is dependent on temperature [28], and, at same time, tomato fruit are capable of photosynthesis and may contribute up 20% to the fruit photosyntate content [34].…”
Section: Plant Growth Yield and Light Efficiencysupporting
confidence: 88%
“…Probably, the differences between LEDs and control treatments was higher for our experiment, because the average external cumulated solar radiation was on average 1900 J cm −2 d −1 for Paucek et al [34], while during our experiment it was 1118 J cm −2 d −1 (data not shown). So, during our experiment, the plants grown only with NL had less light available than during the experiment of Paucek et al [34]. Considering yield, 'Sorentino' was the cultivar with the highest difference between SL and NL conditions, because, as described previously, this cultivar did not differentiate branched inflorescence under NL, while, instead, this occurred for 'Juanita' and 'Solarino' with the reduced advantage of LED application (Figure 7).…”
Section: Plant Growth Yield and Light Efficiencymentioning
confidence: 50%
See 2 more Smart Citations
“…In northern latitudes, solar light levels during the winter can be insufficient to maintain production levels and product quality, due to the low light intensities and short photoperiods ( Davis and Burns, 2016 ). The potential of supplemental lighting to foster off-seasonal production in the Mediterranean region is also now under investigation ( Palmitessa et al, 2020 ; Paucek et al, 2020 ). Under low-light conditions, natural light can be supplemented by artificial lighting, with high pressure sodium (HPS) fixtures currently being the predominant greenhouse lighting source.…”
Section: Introductionmentioning
confidence: 99%